Enteral feeding advancement and growth until 5 years in extremely preterm infants - Cornelia Wiechers; Jan-Niklas Doll; Christoph Maas; Kerstin Gründler; Katja Büchner; Christian F. Poets; Axel R. Franz (BMC, 2021)
Abstract Background In-utero weight gain can be achieved in very preterm infants through rapid advancement of enteral feeds without increasing risk of necrotizing enterocolitis. There are concerns, however, that such rapid weight gain may lead to an increased childhood adiposity risk, although long-term data are sparse. Design This retrospective observational study included two well-characterized cohorts comprising 145 infants born at < 28 weeks or with < 1000 g birth weight. We investigated associations between advancing enteral feeding volumes in daily increments of 15-20 ml/kg (Cohort 1, n = 84, born in 2006/2007) vs. 25-30 ml/kg (Cohort 2, n = 61, born in 2010) and growth up to 5 years of age. Results There was no significant difference in anthropometric parameters post discharge to 5 years between both cohorts. Standard deviation score (SDS) weight and SDS BMI at the age of 5 years remained lower than in the reference population. SDS weight decreased from discharge to about 10-12 months postnatal age and returned to birth values by age 5 years. There was a catch-up for SDS length/height from discharge to 5 years; SDS head circumference decreased from birth to 5 years. Multiple regression analyses revealed that for all anthropometric parameters SDS at birth was the most important predictor for SDS at 5 years. Early parenteral protein intake may be another important factor, at least for head growth. Conclusions Growth was similar in both cohorts without benefit from more accelerated feeding advancement in cohort 2. In both cohorts, early enteral nutrition was associated with in-hospital weight gain as in utero, a drop in weight SDS post discharge and catch-up to birth SDS until age 5 years, remaining below the reference population. Length showed catch-up form discharge to 5 years, whereas head circumference progressively deviated from the reference population. Increased parenteral protein supplementation may be needed to accompany early enteral feeding advancements.